2001
DOI: 10.1038/sj.mp.4000876
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tryptophan hydroxylase and serotonin transporter genes on fluvoxamine antidepressant activity

Abstract: The aim of the present study was to test a possible effect of the A218C tryptophan hydroxylase (TPH) gene variant on the antidepressant activity of fluvoxamine in a sample of major and bipolar depressives, with or without psychotic features. Two hundred and seventeen inpatients were treated with fluvoxamine 300 mg and either placebo or pindolol in a double blind design for 6 weeks. The severity of depressive symptoms was weekly assessed with the Hamilton Rating Scale for Depression. TPH allelic variants were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
2
7

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 57 publications
2
93
2
7
Order By: Relevance
“…The most consistent findings have been of associations between antidepressant treatment response with the insert/delete polymorphism of the upstream regulatory region of the serotonin transporter gene. [39][40][41][42][43][44] Other genes shown to be associated with antidepressant treatment response include tryptophan hydroxylase 45,46 and the serotonin 2 A receptor. 47 Antidepressants act on monoaminergic systems with pharmacological effects that are rapid and biochemically evident within hours of initial drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…The most consistent findings have been of associations between antidepressant treatment response with the insert/delete polymorphism of the upstream regulatory region of the serotonin transporter gene. [39][40][41][42][43][44] Other genes shown to be associated with antidepressant treatment response include tryptophan hydroxylase 45,46 and the serotonin 2 A receptor. 47 Antidepressants act on monoaminergic systems with pharmacological effects that are rapid and biochemically evident within hours of initial drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the 5-HTT gene polymorphism plays a role in the antidepressant response. [3][4][5][6][7] In addition, Mundo et al 8 reported a significant association between the 5-HTTLPR and AIM in bipolar patients treated with proserotonergic compounds. However, the interpretation of this study was limited by the absence of a consensus definition of AIM.…”
Section: Introductionmentioning
confidence: 99%
“…15 Moreover, we reported a worse response for the 5-HTTLPR*s/s subjects to antidepressant treatments. [34][35][36][37][38] We may therefore hypothesize that a given genetic predisposition (5-HTTLPR*s) may confer susceptibility to anxiety features and a worse antidepressant response in subjects affected by mood disorder. Abnormalities in the serotonin transporter function may in fact confer only a small susceptibility to state conditions, because an adaptatory mechanism may partially compensate, while the dramatic alterations of serotonin turnover observed during antidepressant treatment may evidence partial transporter abnormalities, that lead to a worse antidepressant response.…”
mentioning
confidence: 99%